Water Treatment by Coagulation-Flocculation Using Ferric Sulphate as Coagulant - Hary Sulistyo; Wahyudi B Sediawan; Sarto Sarto; Yusuf Yusuf; Ronald Nainggolan (ASEAN Journal of Chemical Engineering, 2012)
Coagulation and flocculation are two essential processes in water treatment. Their improvement on effectiveness and efficiency will give a significant influence for the overall process. The coagulation and flocculation processes involve a coagulant subsequently used to form flocks that can sink precipitate easily. In this research, the sample taken from Sermo Reservoir located in Kulon Progo Regency. The water was containing 320 ppm of colloid and suspended solids. Here, using a magnetic mixer stirrer, 500ml of raw water was mixed with a certain dosage of ferric sulfate in that used as the coagulant at a certain pH in a beaker glass through a high-speed mixing (240 rpm) for five minutes and low-speed mixing (60 ppm) for 10 minutes, respectively. Subsequently, the absorption was measured using UV/Visible. The result then shows 100 ppm for the optimum dosage of ferric sulfate and 9 for the optimum pH. The results indicate that a higher precipitation constant (kd) has resulted in a higher flock diameter. The correlation between the precipitation constant (kd) and the Reynolds number can be expressed as the following equation, kd = 51.98 Re0.3735 with an average relative error of 9.8%.